Genes for a 'Wellderly' Life. Issue 8 (August 2016) - Kauwe, John S.K.; Goate, Alison
Abstract : A long, healthy life is a desire and priority for most people. Genetic factors for longevity do not fully explain healthy aging. Recent research suggests that, in addition to other factors, healthy aging is at least in part the result of protective genetic variants for Alzheimer's disease (AD) and coronary artery disease (CAD).